The double is one of the predominant structures in fantastic orientation narratives. Not only is it related to theories of the fantastic in its conceptual articulation; it also inherits the same problems of context and dissemination of categories. This ar - Sánchez Ávila, Nini Johanna (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The double is one of the predominant structures in fantastic orientation narratives. Not only is it related to theories of the fantastic in its conceptual articulation; it also inherits the same problems of context and dissemination of categories. This article approaches the double as part of a study on fantastic literature in the context of postmodern narratives. For this, the following axes will be considered: multiple concep- tions of the fantastic given since the mid-twentieth century; the transition from modern to postmodern representation; the coincidence between postmodern narrative and representation of the double; the convergence of duplicities; the social double; the double and gender relations, the inefficiency of binary representation, and the deformation of literary doubles in parody and ontological instability